Mammal carcasses attract a swarm of mussels in the deep Atlantic: insights into colonization and biogeography of a chemosymbiotic species. (17th December 2014) - Génio, Luciana; Rodrigues, Clara F.; Guedes, Inês F.; Almeida, Hélio; Duperron, Sébastien; Hilário, Ana
Abstract: Five mammal carcasses were experimentally deployed at 1000 m depth in the Setubal Canyon (NE Atlantic) in March 2011 and the remaining bones were collected after 18 and 28 months. High numbers (1.92–6.27 individuals·cm 2 ) of small mussels were found among a diverse invertebrate assemblage colonizing surfaces, crevices and cavities in the trabecular matrix of bones. In this study we characterized the mussel population and their associated bacteria and investigated population structure and settlement patterns. The results of molecular analysis indicated that the mussels are conspecific with the widely distributed bathymodiolin species ' Idas ' simpsoni and harbor sulfur‐oxidizing bacterial symbionts. Modal decomposition of length‐frequency distributions and estimated shell growth rate suggested that settlement of ' I .'  simpsoni is continuous and that post‐settlement mortality affects the population structure. This study reports the highest densities and fastest growth rates within bathymodiolin mussels occurring on organic substrates yet recorded and provides evidence for effective mussel recruitment in organic falls in the NE Atlantic Ocean. These results highlight the importance of ephemeral habitats on the biogeographic distribution and dispersal of chemosymbiotic species in deep‐sea ecosystems.